Building relationships and negotiating difference in international development volunteerism. Issue 2 (3rd October 2016) - Schech, Susanne; Skelton, Tracey; Mundkur, Anuradha
Abstract : There is growing recognition that building relationships is central to creating sustainable partnerships to achieve meaningful development outcomes. International development volunteers, embedded in the community where they are volunteering, are seen as being ideally placed to build and facilitate these relationships. The nature of international development volunteerism requires both volunteers and host organisations to negotiate through and across cultural difference in order to build mutually beneficial relationships. Three discourses – partnership, globalisation, and everyday encounters with a different culture – frame our analysis of the effort required for effective relationship building. We explore how host organisations and volunteers negotiate difference to build trust and mutual respect as they navigate everyday exchanges and reconcile different expectations and outcomes of volunteerism.